TINJAUAN HUKUM PEMBENTUKAN BADAN USAHA MILIK DESA (BUMDES) DITINJAU DARI UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Ricardo, Tobi (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACTLaw Number 6 of 2014 concerning Villages raises hope for the progress of the Village to increase its role in the economic system. Village-Owned Enterprises are regulated in CHAPTER X Article 87 paragraph 1 of Law Number 6 of 2014 concerning Villages, stating